Gallbladder duplication in a child – case report - Zdanowicz, Katarzyna; Kowalczuk-Krystoń, Monika; Wojtkowska, Małgorzata; Zalewska-Szajda, Beata; Lebensztejn, Dariusz (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Congenital malformations of the gallbladder are rare and may coexist with other abnormalities of the biliary or vascular tree. One such abnormality is duplication of the gallbladder that can be asymptomatic or can present as typical gallbladder pathologies like cholelithiasis, cholecystitis, cholangitis, or pancreatitis. Imaging diagnosis is essential in identifying anatomical abnormalities of the gallbladder. The aim of the presentation is to describe the case of a 16-year-old girl admitted to hospital with abdominal pain. Abdomen ultrasound and magnetic resonance cholangiopancreatography detected a duplicated gallbladder. In the patient other clinical, laboratory, and radiological features of the gallbladder or bile duct pathology were not observed. In the case of this congenital anomaly, if it occurs asymptomatically, conservative and surgical treatment is not indicated.